Efficient hydrogen evolution by reconstruction of NiMoO4–CoO via Mo recombination. Issue 12 (9th May 2022) - Teng, Juejin; Dong, Zhixin; Liu, Daokun; Zhang, Xiao; Guo, Jinxue
Abstract : Surface reconstruction in NiMoO4 –CoO nanosheet catalyst through Mo dissolution with subsequent formation of K2 Mo3 O10  is disclosed, which brings more active sites and enhanced charge transfer, and boosts intrinsic HER activity per catalysis site. Abstract : Surface reconstruction of oxygen evolution reaction electrocatalysts with enhanced catalysis activity has been intensively reported recently. However, the surface reconstruction has seldom been observed from hydrogen evolution reaction (HER) catalysts. Here, we report the surface reconstruction with enhancement of catalysis activity in the HER catalyst of NiMoO4 –CoO nanosheets on carbon cloth. Mo species dissolve from NiMoO4 –CoO by activating the pristine catalyst at certain potential, which enables the formation of K2 Mo3 O10 on the catalyst surface. The surface reconstruction not only brings large numbers of active sites and enhanced charge transfer, but also boosts the intrinsic activity per catalysis site. Together with the above advantages and the benefits of nanosheet structure, the activated catalyst exhibits high HER activity with the ultralow overpotentials of 130 and 192 mV at high current densities of 100 and 400 mA cm −2 . This finding provides new insight for the exploration on surface reconstruction of transition metal-based HER catalysts and may enable further understanding on the origin of catalysis activity improvement.